Pengaruh Teori Van Hiele Terhadap Hasil Belajar pada Materi Mengidentifikasi Sifat-Sifat Bangun Ruang - putri, dini Arentina; Ahmad, Syafri; Desyandri, Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This research is done due to teachers lack of knowledge and ability in implementing the Van Hiele theory in the learning process of identifying solid figures’ characteristics. It aims at finding out the effects of the theory toward students’ learning outcomes at class V Gugus 8 SD Kuranji, Padang. This quasi experiment applied the purposive sampling technique to select the samples. Class V of SDN 41 Kuranji was selected as the experimental class while class VA of SDN 50 Kuranji acted as the control one. Date were obtained  from a multiple-choice test. They were analyzed by using the t-test formula. Based on the results of research conducted, obtained the average value of the experimental class pretest of 63.52 and the average value of the control class pretest of 65.05. While the average posttest value of the experimental class is 86.00 and the average posttest value of the control class is 81.05. From the results of the pretest and posttest scores of the two sample classes, the experimental class increased by 22.48 while the control group experienced an increase of 16.00. From the results of the t-test with a significant level (α = 0.05) in the experimental class with the acquisition of tcount of 7.61 and ttable 1.68 this means thitung> t table. So it can be concluded that the use of Van Hiele theory has a good effect the students’ learning outcomes indentifying solid figures’ characteristics. Keywords:  Learning Outcomes, The Van Hiele Theory